Predictors of atrial fibrillation following coronary artery bypass surgery - Gjerakaroska Radovikj, Marija; Srbinovska Kostovska, Elizabeta; Gjerakaroska-Savevska, Cvetanka; Jovev, Sashko (Scientific Foundation SPIROSKI, 2020)
Atrial fibrillation (AF) is the most common type of arrhythmia following open heart surgery and it contributes to prolonged hospital stay, increased prevalence of thromboembolic complications and overall increased postoperative morbidity and mortality. The aim of this prospective observational follow-up study was to determine the incidence of postoperative atrial fibrillation (POAF) in patients undergoing coronary artery bypass surgery, to identify predisposing  risk factors for its occurrence in the immediate preoperative period and to assess its effect on the postoperative outcome in patients at the University Clinic for Cardiac Surgery in Skopje, North Macedonia. Material and methods: The study included patients at the University Clinic for Cardiac Surgery in Skopje, North Macedonia undergoing coronary artery bypass surgery. The experimental group included patients developing POAF, whereas the control group those who did not develop the primary outcome. All patients were followed up for a period of 30 days postoperatively. Results: POAF was registered in 38% of the patient population and more frequently in the elderly. Patients developing POAF had significantly higher left atrial volume index, as well as higher CHADS2-VASC2, HATCH and Euroscore I values. Average time to POAF occurrence was 48-72 hours postoperatively. There were death outcomes, thromboembolic events, longer hospital stay, need for antiarrhythmic and oral anticoagulant therapy in the POAF group. Conclusion: POAF significantly increases postoperative morbidity and mortality in patients undergoing coronary artery bypass surgery. Age, higher CHADS2-VASC2, HATCH and Euroscore I values and left atrial volume were found to be significant predictors of POAF after coronary artery bypass surgery.